The Impact of Mass Media in Using Contraceptives among Married Males-A study from Hatiya VDC of Makawanpur, Nepal - Pandey, Srijana; Karki, Supendra (Asian Journal of Medical Sciences, 2010)
Objectives: To analyze the association between exposure to mass media and use of contraceptive. Methods: In this cross sectional descriptive study, 387 married males of Hatiya VDC were randomly selected. This study uses semi-structured questionnaire to acquire information regarding background character of respondents and the exposure of family planning message to mass media. Results: Both print and electronic media were found major reproductive health information dissemination tools. Exposure was positively related to age, education level, income, partner approval and discussed family planning with partner. There was no significant difference in exposure based on number of living children. Conclusion: Findings from this study are consistent with the interpretation that mass media promotion of the family planning message motivated sexual partners to discuss use of the contraceptives, and that discussion exerted a strong influence on their intention to use it. The programmatic implications of these findings are that multiple media channels should continue to be used to promote family planning and other reproductive health issues. Priority should be given to media channels that reach large numbers of the intended audience, but supporting channels (such as print and interpersonal communication) should also be included in the media mix. Key words: Mass media; Contraceptives DOI: 10.3126/ajms.v1i1.2928 Asian Journal of Medical Sciences Vol.1(1) 2010 p.9-11